Characterization of ZAT12 protein from Prunus persica: role in fruit chilling injury tolerance and identification of gene targets - Gismondi, Mauro (2025)
ZAT (zinc finger of Arabidopsis thaliana) proteins play roles in multiple abiotic stress tolerance in Arabidopsis and other species; however, there are few reports on these transcription factors (TFs) in fruit crops. This study aimed to evaluate PpZAT12, a C2H2 TF up-regulated in peach fruit by a heat treatment applied before postharvest cold storage for reducing chilling injury (CI) symptoms. Here, the expression of PpZAT12 in different tissues and fruits subjected to either postharvest heat or cold treatments, was evaluated in peach varieties with differential susceptibility to develop CI. PpZAT12 increased by cold storage in CI-resistant cultivars (‘Elegant Lady’ and ‘Rojo 2’), while it was not modified in a cultivar susceptible to develop CI (‘Flordaking’). Besides, we expressed PpZAT12 in Arabidopsis (35S::PpZAT12) and found that these plants show impaired plant growth and development, rendering small plants with senescence delay and aborted seeds. We applied a proteomic approach to decipher the peptides responding to PpZAT12 in Arabidopsis and found 348 differential expressed proteins (DEPs) relative to the wild type. Besides, comparing the DEPs between Arabidopsis plants expressing PpZAT12 or AtZAT12 (35S::AtZAT12) we found common and specific responses to these TFs. Based on the proteomic information obtained here and published data about AtZAT12, we searched ZAT12-targets in peach allowing the identification of a putative ZAT12 regulon in this species. The identified peach ZAT12-protein targets could underlie the differential susceptibility to CI among different peach varieties and can be used as future targets to improve adaptation to refrigeration in fleshy fruits.